2020
DOI: 10.3892/mmr.2020.11704
|View full text |Cite
|
Sign up to set email alerts
|

Effects and molecular mechanism of pachymic acid on ferroptosis in renal ischemia reperfusion injury

Abstract: Acute kidney injury (AKI) is a common clinical disease. Ferropotosis, a new type of regulatory cell death, serves an important regulatory role in AKI. Pachymic acid (PA), a lanostane-type triterpenoid from Poria cocos, has been reported to be protective against AKI. However, the protective mechanism of PA in AKI is not yet fully understood. The present study aimed to investigate the effect and molecular mechanism of PA on ferroptosis in renal ischemia reperfusion injury in vivo. A total of 30 mice were intrape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 39 publications
1
42
0
Order By: Relevance
“…According to research, under the treatment of pachymic acid, the renal function of mice with renal I/R injury can be improved, and renal injury can be alleviated. The protective effect of pachymic acid may be related to the inhibition of renal ferroptosis through directly or indirectly activating Nrf2 and upregulating downstream GPX4, system x c − , and HO-1 [ 110 ]. Additionally, XJB-5-131 is a mitochondrial-targeted nitroxide with a high affinity for tubular epithelial cells [ 111 ].…”
Section: Pathological Mechanisms and Potential Targeted Therapy Of Ferroptosis In Ischemia-reperfusion Injurymentioning
confidence: 99%
“…According to research, under the treatment of pachymic acid, the renal function of mice with renal I/R injury can be improved, and renal injury can be alleviated. The protective effect of pachymic acid may be related to the inhibition of renal ferroptosis through directly or indirectly activating Nrf2 and upregulating downstream GPX4, system x c − , and HO-1 [ 110 ]. Additionally, XJB-5-131 is a mitochondrial-targeted nitroxide with a high affinity for tubular epithelial cells [ 111 ].…”
Section: Pathological Mechanisms and Potential Targeted Therapy Of Ferroptosis In Ischemia-reperfusion Injurymentioning
confidence: 99%
“…The second synergistic effect of ERL + CDODA-Me was indicative of oxidative stress events such as ferroptosis, which is typically associated with the upregulation or downregulation of iron-related transcripts, such as heme oxygenase-1 [ 54 , 55 ], ferritin heavy chain 1 (FTH1) [ 56 ], transferrin receptor 1, ferroportin, and altered expression of glutathione-related genes such as cystine/glutamate transporter xc(-) (SLC7A11), glutathione peroxidase 4 (GPX4), and glutamate-cysteine ligase, which are regulated by Nrf2 transcription in response to oxidative stress. ERL + CDODA-Me results in upregulation in Nrf2, similar to that observed as a survival response triggered by the presence of oxidative dangers by elevating intracellular glutathione-related antioxidant systems [ 57 ]. Drugs that act as iron chelators or ferroptosis inhibitors [ 58 , 59 ] can inhibit cell death, while inhibition of cysteine uptake, attenuation of glutathione transferases, or inactivation of GPX4 can exacerbate it [ 60 ].…”
Section: Discussionmentioning
confidence: 80%
“…Similarly, we found that levels of GSH were higher when either CIRBP or ELAVL1 were suppressed and lower when ferroptosis was increased. Recently, Jiang et al 40 found that pachymic acid increased levels of GSH expression and lowered ferroptosis in a murine model of IR. They proposed that a possible mechanism could be through the activation of NRF2.…”
Section: Discussionmentioning
confidence: 99%